Different Faces in the Crowd: A Happiness Superiority Effect for Schematic Faces in Heterogeneous Backgrounds - Craig, B.; Becker, S.; Lipp, Ottmar (American Psychological Association, 2014)
Recently, D.V. Becker, Anderson, Mortensen, Neufeld, and Neel (2011) proposed recommendations to avoid methodological confounds in visual search studies using emotional photographic faces. These confounds were argued to cause the frequently observed Anger Superiority Effect (ASE), the faster detection of angry than happy expressions, and conceal a true Happiness Superiority Effect (HSE). In Experiment 1, we applied these recommendations (for the first time) to visual search among schematic faces that previously had consistently yielded a robust ASE. Contrary to the prevailing literature, but consistent with D.V. Becker et al. (2011), we observed a HSE with schematic faces. The HSE with schematic faces was replicated in Experiments 2 and 3 using a similar method in discrimination tasks rather than fixed target searches. Experiment 4 isolated background heterogeneity as the key determinant leading to the HSE.